Dysregulation of Principal Circulating miRNAs in Non-human Primates Following Ischemic Stroke - Chen, Jian; Zhao, Haiping; Huang, Yuyou; Li, Yuqian; Fan, Junfen; Wang, Rongliang; Han, Ziping; Yang, Zhenhong; Wu, Longfei; Wu, Di; Luo, Yumin; Ji, Xunming (Frontiers in Neuroscience, 2021)
Despite the recent interest in serum microRNA (miRNA) biomarkers in acute ischemic stroke patients, there is limited knowledge about the miRNAs directly related to stroke itself due to the multiple complications in patients, which has hindered the research progress of biomarkers and therapeutic targets of ischemic stroke. Therefore, in this study, we compared the differentially expressed miRNA profiles in the serum of three rhesus monkeys pre- and post-cerebral ischemia. After cerebral ischemia, RFAM sequence category revealed increased ribosomic RNA (rRNA) and decreased transfer RNAs (tRNAs) in serum. Of the 2049 miRNAs detected after cerebral ischemia, 36 were upregulated, and 76 were downregulated (fold change ≥2.0, P <0.05). For example, Mml-miR-191-5p, miR-421, miR-409-5p, and let-7g-5p were found to be significantly overexpressed, whereas mml-miR-128a-5p_R-2, miR-431_R-1, and let-7g-3p_1ss22CT were significantly downregulated. Gene ontology and Kyoto Encyclopedia of Genes and Genomes (KEGG ) pathway analyses revealed that these differentially expressed miRNAs were implicated in the regulation of ubiquitin-mediated proteolysis and signaling pathways in cancer, glioma, chronic myeloid leukemia, and chemokine signaling. miRNA clustering analysis showed that mml-let-7g-5p and let-7g-3p_1ss22CT, which share three target genes (RB1CC1, GNG5, and CXCR4), belong to one cluster, were altered in opposite directions following ischemia. These data suggest that circulating mml-let-7g may serve as a therapeutic target for ischemic stroke.